2016
DOI: 10.1155/2016/5724973
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Potentials of Plant‐Derived Small Molecules against Doxorubicin Associated Cardiotoxicity

Abstract: Doxorubicin (DOX) is a potent and widely used anthracycline antibiotic for the treatment of several malignancies. Unfortunately, the clinical utility of DOX is often restricted due to the elicitation of organ toxicity. Particularly, the increased risk for the development of dilated cardiomyopathy by DOX among the cancer survivors warrants major attention from the physicians as well as researchers to develop adjuvant agents to neutralize the noxious effects of DOX on the healthy myocardium. Despite these pitfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 139 publications
3
56
0
Order By: Relevance
“…Inflammation, oxidative stress, and apoptosis are reported to participate in DOX-induced cardiotoxicity; 23 therefore, we subsequently investigated the protective activity of FGF21 against DOX-induced inflammation, oxidative stress, and apoptosis in the H9c2 cell line and adult mouse cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation, oxidative stress, and apoptosis are reported to participate in DOX-induced cardiotoxicity; 23 therefore, we subsequently investigated the protective activity of FGF21 against DOX-induced inflammation, oxidative stress, and apoptosis in the H9c2 cell line and adult mouse cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, quercetin protected also primary cultures of rat cardiomyocytes and H9c2 cells against the anticancer agents doxorubicin (DOX) and daunorubicin, well-known to induce acute and long-term cardiotoxicity [28][29][30][31].…”
Section: Flavonolsmentioning
confidence: 99%
“…1,6 Accordingly, much attention is being paid to find novel antioxidant for combination regimens against the oxidative stress-triggered cardiomyopathy in DOX therapy, especially those plant-derived small molecules with considerable safety. 9 Curcumin (CUR) is a kind of natural antioxidant derived from the perennial herb Curcuma longa, and some research has highlighted its potency as an ROS scavenger. 10 Available laboratory evidence also confirmed that cardiotoxicity as a result of acute DOX exposure could be reduced by CUR supplementation both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%